2012
DOI: 10.1111/j.1752-4571.2012.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide cycling has diverse effects on evolution of resistance in Chlamydomonas reinhardtii

Abstract: Cycling pesticides has been proposed as a means of retarding the evolution of resistance, but its efficacy has rarely been empirically tested. We evolved populations of Chlamydomonas reinhardtii in the presence of three herbicides: atrazine, glyphosate and carbetamide. Populations were exposed to a weekly, biweekly and triweekly cycling between all three pairwise combinations of herbicides and continuously to each of the three herbicides. We explored the impacts of herbicide cycling on the rate of resistance e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 61 publications
(97 reference statements)
3
46
1
Order By: Relevance
“…Brotherton et al established differences in sensitivity to glyphosate between accessions of A. thaliana and tried (but failed) to select for decreased sensitivity. Others have used the single‐celled chlorophyte Chlamydomonas reinhardtii as a model for exploring the evolutionary dynamics of selection for herbicide resistance . The Chlamydomonas system has proved a useful tool for exploring the efficacy of resistance management prescriptions in delaying evolution of resistance, although questions remain about the translation of findings to higher plants.…”
Section: Studying Evolution In Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brotherton et al established differences in sensitivity to glyphosate between accessions of A. thaliana and tried (but failed) to select for decreased sensitivity. Others have used the single‐celled chlorophyte Chlamydomonas reinhardtii as a model for exploring the evolutionary dynamics of selection for herbicide resistance . The Chlamydomonas system has proved a useful tool for exploring the efficacy of resistance management prescriptions in delaying evolution of resistance, although questions remain about the translation of findings to higher plants.…”
Section: Studying Evolution In Actionmentioning
confidence: 99%
“…The potential benefits of herbicide rotations and mixtures have been demonstrated by a number of empirical and theoretical studies. However, most of these studies have considered the evolution of specialist resistance phenotypes, where selection for discrete resistance traits is independent.…”
Section: Rotations Sequences and Mixturesmentioning
confidence: 99%
“…We have previously shown that resistance to carbetamide is very costly and is not easily acquired by a wild-type population [19]. Epistatic interactions between independent resistance mutations can affect the fitness costs [15], so that presence of resistance mutations to one xenobiotic could reduce the costs associated with resistance to a subsequent herbicide through antagonistic epistasis between resistance mutations [12,25].…”
Section: Discussionmentioning
confidence: 99%
“…The strain was pre-adapted to laboratory culture conditions and, prior to selection experiments, a selection line was initiated by isolating a single cell colony from an agar plate and subsequent multiplication for 7 days in liquid Bold's medium [19].…”
Section: Materials and Methods (A) Founding Populationmentioning
confidence: 99%
See 1 more Smart Citation